Condition Optimization for The Analysis of Risperidone and 9-0H-Risperidone by High-Performance Liquid Chromatography - Luki Yogaswara Yusuf; Aliya Nur Hasanah; Melisa Intan Barliana (Medical Laboratory Technology Journal, 2022)
Risperidone (RIS) is one of the most widely used atypical antipsychotics for treating schizophrenia in hospitals. RIS is metabolized by the liver and produces the primary active metabolite  9-OH-Risperidone (9-OHR). In the process of RIS metabolism, it is suspected that there are gene polymorphisms that cause variations in patient responses. Analysis of RIS and 9-OHR levels in the patient's blood can help to explain the various responses. High-Performance Liquid Chromatography (HPLC) is the most popular method to analyze RIS and 9-OHR, but many deficiencies were found in the chromatograms in the previous study. This research aims to obtain optimal conditions of the analysis prior to method validation. Condition optimization by optimizing the wavelength, composition of the mobile phase, pH, flow rate, and particle size of the stationary phase. The results showed that the wavelength was 279 nm, the mobile phase was 0.05 M KH2PO4 pH 3.7: acetonitrile (94:6, v/v) plus 0.3% triethylamine, and the flow rate was 1.2 ml/min in the stationary phase (LiChroCART® RP 18; 250x4 mm; 10 µm) being the optimal condition. This method is suggested to continue method validation for analyzing RIS and 9-OHR in the serum or plasma.